Effects of habitat heterogeneity on epiedaphic Collembola (Arthropoda: Hexapoda) in a semiarid ecosystem in Northeast Brazil - Ferreira,Aila Soares (2018)
ABSTRACT The spatial distribution of abiotic resources and environmental conditions can vary at small scales within terrestrial ecosystems, influencing the composition of soil fauna. Epiedaphic springtails (Collembola) of a semiarid Caatinga ecosystem were studied to determine if factors related to vegetation structure, such as species richness, aerial biomass, litterfall, and soil characteristics (pH, granulometry and soil organic matter), influence species richness and abundance of this group. A total of 5,513 individuals were collected of 15 species distributed in 13 genera and 9 families. The most abundant species were Temeritas sp., with 2,086 (38% of the total abundance) individuals, and Neotropiella meridionalis (Arlé, 1939), with 1,911 (35% of the total abundance) individuals. None of the variables in the regression model were significantly related to Collembola species richness, but abundance was significantly related to plant species richness, aerial biomass and soil pH. Thus, even at a small spatial scale, habitat heterogeneity influences the epiedaphic Collembola in the Caatinga ecosystem, especially their abundance.